PENGARUH MODAL INTELEKTUAL TERHADAP ROE dan EPS SEBAGAI PROKSI KINERJA KEUANGAN (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2011 - 2013) - Osmad Muthaher; Iwan Nur Prasetyo (Jurnal Ekonomi dan Bisnis, 2014)
The purpose of this study is to provide empirical evidence about the influence of intellectual capital on the financial performance of the company. This study uses a model Pulic (Value Added Intellectual Coefficient - VAICTM) were identified into three components, namely, capital employed efficiency (CEE), human capital efficiency (HCE) and structural capital efficiency (SCE). This study examines the effect of the three components of the Return On Equity (ROE) and Earnings Per Share (EPS) as the company’s financial performance. The data used in this study is a secondary data from company financial reports in 2011-2013 were obtained from theIndonesia Stock Exchange (IDX). The sample was 53 companies in 3 years, bringing the total sample 159. Samples were taken using purposive sampling method and which meet the criteria of sample selection. The results of this study indicate that: (1) Capital Employed Efficiency (CEE) significant positive effect on return on equity (ROE) and Earnings Per Share (EPS). (2) Human Capital Efficiency (HCE) significant positive effect on EPS and no effect on ROE. (3) Structural Capital Efficiency (SCE) significant positive effect on ROE and no effect on EPS.Keywords: capital employed efficiency, Earning Per Share (EPS), efficiency of human capital, return on equity (ROE) structural capital efficiency.